ELT Students’ Perceptions of Classroom Management during Teaching Practice: Difficulties and Solutions - Joeang Salsabiltisa De Side; Mohammad Adnan Latief; Ekaning Dewanti Laksmi (Universitas Negeri Malang, 2021)
Abstract: Teaching practice becomes one of the challenges for ELT student teachers to carry out the theories they have learned into practice. In view of the challenges, ELT student teachers of Universitas Negeri Malang may also have difficulties in managing a classroom. Therefore, this study was conducted to know the ELT students’ perceptions of classroom management during teaching practice, focusing on the difficulties and solutions. A quantitative with a descriptive research survey was used as the research design. An online questionnaire and interview were used as the instruments to collect the data. The result of this study shows that ELT student teachers 2016 of Universitas Negeri Malang have many difficulties in setting the rules and procedures, especially for group work. The result of the questionnaire depicts that some students break the rules (83.4%), difficulties in handling students who were not willing to work with their friends (67.9%), difficulties in ending the teaching and learning activity that reinforces discipline (66.7%), difficulties in engaging students’ interests at the beginning of teaching and learning activity (57.1%), and difficulties in handling students who bother their friends when they have finished a task (51.2%). For ELT student teachers who will be doing their teaching practice, it is essential to understand and deepen the knowledge of managing the classroom. Moreover, student teachers need to set clear instructions for group work and negotiate with the students whether they want to make groups by themselves or randomly chosen by the teacher. Lastly, give extensive activities for “disruptive students”. Keywords: student teachers, teaching practice, classroom management Abstrak: Praktik mengajar menjadi salah satu tantangan bagi mahasiswa ELT untuk mengimplementasikan teori-teori yang telah dipelajarinya. Melihat tantangan tersebut, mahasiswa ELT Universitas Negeri Malang sebagai calon guru mungkin juga mengalami kesulitan dalam mengelola ruang kelas. Oleh karena itu, penelitian ini dilakukan untuk mengetahui persepsi mahasiswa ELT tentang pengelolaan kelas selama praktik mengajar, fokus pada kesulitan dan solusi. Penelitian ini menggunakan metode kuantitatif, survei deskriptif. Instrumen yang digunakan untuk mengumpulkan data adalah angket dan wawancara. Hasil penelitian ini menunjukkan bahwa mahasiswa KPL Pendidikan Bahasa Inggris Universitas Negeri Malang tahun ajaran 2016 mengalami banyak kesulitan dalam menetapkan tata tertib dan prosedur di dalam kelas selama praktik mengajar, terutama saat kerja kelompok. Hasil kuesioner menunjukkan bahwa mahasiswa KPL mengalami kesulitan dalam menetapkan aturan dan tata cara kerja kelompok karena ditemukan beberapa siswa yang tidak patuh (83,4%), kesulitan dalam menangani siswa yang tidak mau bekerja dengan temannya ( 67,9%), kesulitan dalam mengakhiri kegiatan belajar mengajar yang melatih kedisiplinan (66,7%), kesulitan dalam menarik minat belajar siswa pada awal pembelajaran (57,1%), dan kesulitan menangani siswa yang mengganggu temannya saat mereka telah menyelesaikan tugasnya (51,2%). Bagi mahasiswa KPL Pendidikan Bahasa Inggris yang akan praktik mengajar, sangat penting untuk memahami dan memperdalam ilmu pengelolaan kelas. Selain itu, mahasiswa KPL perlu memberikan instruksi yang jelas saat kerja kelompok dan bernegosiasi dengan siswa apakah mereka ingin membuat kelompok sendiri atau dipilih secara acak oleh guru. Untuk “siswa yang mengganggu”, mahasiswa KPL dapat memberikan tugas tambahan. Kata kunci: guru siswa, praktik mengajar, manajemen kelas